Laying and growth performance of local chicken (Gallus gallus domesticus) ecotype Konde in Burkina Faso - Yacouba, ZARE; B. Isidore, GNANDA; Michel, KERE; Boureima, TRAORE; Isidore, HOUAGA; F. Boris, SANON; jumeau, ILBOUDO W. Fernand 1er; M. C. Valérie, BOUGOUMA-YAMEOGO; Romdhane, REKAYA; A. Joseph, NIANOGO (International Journal of Environment, Agriculture and Biotechnology, 2023)
Limited information exists regarding the zootechnical performance of the local chicken ecotype Konde. The objective of this study was to evaluate the laying and growth performance of local hens Gallus gallus domesticus ecotype Konde in a semi-intensive production system. A founder group of breeders (30 hens and 6 roosters) from the Boulgou Province (Garango, Zabré and Tenkodogo) was set up at a ratio of one (1) rooster for five (5) hens. Eggs were collected and identified daily. After five days of collection, eggs were naturally incubated under large brood hens (15 to 20 eggs) and then transferred to a compartmentalized and numbered hatcher. These incubations resulted in 306 identifiable one-day-old chicks (106 in the wet season, 103 in the cold dry season and 100 in the hot dry season). The individual weight (IW) of the chicks was recorded every week from hatching to three (3) months of age. Carcass characteristics were assessed on 10 birds per rearing period at 3 months of age. The laying rate was 33.60% during a 180-day laying period. Observed fertility and hatching rates were 60.33 and 80.31%, respectively. The average weight, length and large diameter of the eggs were 41.33 g, 48.75±2.07mm and 36.42±1.6mm, respectively. The results showed that chicks with an average hatching weight of around 28g reached, at three months of age, 926.64 ± 153 g, 884.06 ± 133 g, and 857.44 ± 105 g during the rainy, cold-dry, and hot-dry seasons, respectively. Carcass yield was 62.19, 66.46, and 65.91% in the rainy, hot, and dry seasons, respectively. A detailed economic evaluation showed a gross profit of 922 FCFA per bird at 3 months of age. Based on the growth performance, the local chicken ecotype Konde could be used for meat production. However, further improvement of performance and sustainability of the chicken’s ecotype Konde through genetic selection and management tools is still needed.